2018
DOI: 10.1186/s12935-018-0597-9
|View full text |Cite
|
Sign up to set email alerts
|

B7-H4 overexpression contributes to poor prognosis and drug-resistance in triple-negative breast cancer

Abstract: BackgroundThe expression of the immunoregulatory protein B7-H4 has been reported in many types of cancer, including breast cancer. However, its role in triple-negative breast cancer (TNBC), especially its correlation with patients’ prognosis and chemoresistance remains unclear.MethodsThe expression of B7-H4 in TNBC tissues and cell lines were measured with Real-Time PCR and western blotting. 65 cases of TNBC tissue samples and adjacent non-tumor tissue samples were analyzed by immunochemistry to demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 59 publications
1
32
0
Order By: Relevance
“…Incubated T cells with B7S1-Ig fusion protein in vitro significantly inhibits the proliferation and cytotoxic activity of T cells, by interfering with the activation of ERK, JNK, and AKT (Wang et al, 2012;Wang and Wang, 2020). B7S1 silencing enhanced drug-induced apoptosis by inhibiting the PTEN/ PI3K/AKT pathway in triple-negative breast cancer cells (Wang et al, 2018). Furthermore, blockade of B7S1 downregulated the transcription of CXCL12/CXCR4.…”
Section: Introductionmentioning
confidence: 98%
“…Incubated T cells with B7S1-Ig fusion protein in vitro significantly inhibits the proliferation and cytotoxic activity of T cells, by interfering with the activation of ERK, JNK, and AKT (Wang et al, 2012;Wang and Wang, 2020). B7S1 silencing enhanced drug-induced apoptosis by inhibiting the PTEN/ PI3K/AKT pathway in triple-negative breast cancer cells (Wang et al, 2018). Furthermore, blockade of B7S1 downregulated the transcription of CXCL12/CXCR4.…”
Section: Introductionmentioning
confidence: 98%
“…Huang et al showed that the OS rate of patients with higher B7-H4 expression was signi cantly worse than in those with lower expression [18]. Similarly, TNBC patients with B7-H4 overexpression had signi cantly shorter survival and recurrence time than those with low B7-H4 expression [19]. These data suggest that B7-H4 might be a potential negative prognostic indicator.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple mechanisms by which B7-H4 can affect tumor cell biology. Wang et al (34) reported that silencing B7-H4 enhances drug-induced apoptosis by inhibiting the phosphatase and tensin homolog (PTEN)/PI3K/AKT signaling pathway, indicating the role of B7-H4 in chemoresistance and suggesting that it may be an attractive therapeutic target in triple-negative breast cancer. Xie et al (15) demonstrated that B7-H4 induced epithelial-mesenchymal transition, and promoted invasion and metastasis of tumor cells by the activation of the ERK1/2 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that B7-H4 is upregulated in several types of cancer ( 28 31 ), which suggests that B7-H4 has the potential to be used as a biomarker or therapeutic target for tumors ( 19 , 31 33 ). However, other studies revealed that B7-H4 promotes cell proliferation ( 34 , 35 ), invasion and metastasis of tumor cells ( 15 , 35 , 36 ), enhances leukemia-initiating cell differentiation ( 23 ), and is correlated with carcinogenesis and chemoresistance ( 34 , 37 ).…”
Section: Discussionmentioning
confidence: 99%